Integrating Indigenous Traditions into Character Education: Insights from Primary School Teachers - Suparjan Suparjan; Tawakkal Tawakkal; Andi Eliyah Humairah; Harpina Harpina; Tahmid Madjid; Nining Ismiyani; Irman Syarif (Ta'dib, 2024)
This research aims to explore how primary school teachers integrate character education based on indigenous cultures and traditions in elementary school settings. Using a qualitative approach, the study involved collecting and analyzing data through semi-structured interviews with eight educators. The procedure included gathering information, reducing and presenting data, and drawing conclusions to understand how teachers incorporate local traditions and cultures from the Malay and Dayak tribesÔÇösuch as Pengari, Saprahan, Beduruk, Robok-robok, Beroyong and Jagau SungeiÔÇöinto their teaching practices. The findings reveal that teachers adapt these traditions to promote character development, focusing on values like cooperation, mutual assistance, responsibility, social care, and environmental consciousness. This study contributes novel insights into the practical application of indigenous cultural elements in character education and demonstrates how these practices can enhance student development and cultural awareness.